Tongue-tied modernism in Jean Rhys's Paris. Issue 7 (9th August 2019) - Williams, James
ABSTRACT: Jean Rhys's four early novels, written in Paris and London in the inter-war years, take a self-consciously peripheral position in relation to the high modernist experimentation which surrounded their composition. Rhys deploys the interiority, stream-of-consciousness and linguistic defamiliarisation of her modernist peers, but also challenges their perceived primacy of form, as well as the suitability of modernist aesthetics for representing social and political realities. Rhys's multilingualism is a characteristic of her style, but also a means of considering the apparent unravelling of form in Quartet and Good Morning, Midnight as a productive gesture.